Analisis dan Perancangan Sistem Informasi Kartu Nelayan Untuk Masyarakat Kabupaten Bangka Barat Berbasis Desktop Studi Kasus: Dinas Kelautan dan Perikanan Kabupaten Bangka Barat - Kiswanto Kiswanto; Andi Andi (ISB Atma Luhur, 2017)
Dinas Kelautan dan Perikanan are elemental Local Government executor at naval area and fishery and on hands to Regent via Region secretary. Dinas Kelautan dan Perikanan having task is region autonomy at naval area and fishery covers sumberdaya's management fishery and naval, coast and isle in order to perform pembantuan's decentralisation and task task. Fishery area and Catches is one of area in on duty naval and fishery that services in makings and Fisherman Card exploit. Therefore fishery Area and Catches to have gets to give prima service and can in cards harnessed management fisherman to fishermen on the nose utilised and correct objective. One of effort which can be done is increase and do harnessed information system repair fisherman card with computerised and integrated system to be able to give information in point and accurate basal succeeding decision making.